Vibration transmission through joints of walls and columns in framed buildings - Mickaitis, Marius; Stauskis, Vytautas J. (Journal of Civil Engineering and Management, 2005)
Constructional practice has shown that structure‐borne sound transmission through joints can signally reduce airborne sound insulation in buildings. Vibration transmission coefficient evaluates this reduction in design calculations. In this article sound transmission through joints in framed buildings is investigated. Rooms in framed buildings are shaped by walls and ceilings connected to columns. Several walls could be connected to each column in a building plan. Such joints are modelled like idealised plate–beam–plate junctions. Examining vibration transmission through these junctions, the influence of a column must be estimated. The column will resist forces and moments applied by the connected walls. The aim of the paper is to evaluate how various properties of walls and columns influence the vibration transmission loss at joints of buildings. The results are compared with the results of similar junctions without columns. Vibracijų sklidimas karkasinių pastatų sienų ir kolonos mazguose Santrauka. Statybos praktika parodė, jog struktūrinio‐orinio garso sklidimas pro mazgus dažniausiai būna veiksnys, galintis labai sumažinti orinio garso izoliaciją pastatuose. Projektiniais skaičiavimais jis nustatomas pagal vibracijų perdavimo koeficientą. Analizuojamas garso sklidimas pro karkasinio pastato mazgus. Patalpos pastatuose yra formuojamos iš sienų ir perdangų, kurios jungiasi prie kolonų. Pastato plane prie kolonos gali būti prijungta keletas sienų, taip suformuojant įvairių formų mazgus. Tokie mazgai modeliuojami kaip idealizuotos plokštės‐strypo‐plokštės jungtys. Tiriant garso sklidimą pro tokius mazgus, reikia įvertinti ir kolonos įtaką. Darbo tikslas yra nustatyti, kokią įtaką įvairūs sienų ir kolonos parametrai turi garso sklidimui pastatuose pro mazgus. Rezultatai lyginami su analogiškų mazgų be kolonos tyrimų rezultatais. Raktiniai žodžiai: struktūrinė akustika, vibracijos, struktūrinis‐orinis triukšmas, perdavimo nuostoliai. First Published Online: 14 Oct 2010